KEBIJAKAN KRJMINAL DALAl\1 MENANGGULANGI KEJAHATAN PERDAGANGAN ANAK DI BAWAH UMUR - M. Chairul Idrah (Universitas Batanghari Jambi, 2011)
Crimrnal pohcres m tackling traffickmg mmors is done by applying precaution (prevention), measures of protection (protection) against the victim and law enforcement action (Prosecutmn) to the perpetrators (traffickers) are realized with the enactment of Presidential Decree Number 88 Year 2002 on Plan National Action Elimination of Trafficking of Women and Children (RAN P3A)Keyword. Poverty, Cnme. Trajfickmg in Children